Narrativas de professoras da educação básica: entrelaces da prática pedagógica com a diversidade - Lopes, Maria da Conceição Oliveira (2022)
This study aims to understand, from the teachers' narratives, how diversity crosses the area of pedagogical practice of teachers from Basic Education.The concerns that mobilized the research arise within the scope of the work of school management and are related to the intention of knowing how the educational processes with human diversity occur in the daily life of the classroom, in order to problematize how the conceptions, perceptions of diversity cross the teaching narratives, in order to reflect on the importance of a pedagogy of diversity, interculturally oriented. The research collaborators are five language teachers who work in a big public school in the countryside of Bahia, a northeast state of Brazil and who carry out social teaching activities and projects, deserving an understanding of their work with language in a disadvantaged and diverse school context, in the human dimension. The theoretical foundations are anchored in two central categories, teacher training and diversity. To consolidate the first axis, teacher training, and the categories that unfold from it, such as permanent training and pedagogical practices, we dialogue with Nóvoa (2014), Imbernón (2011); Josso; Pineau (2014), Silva; Rivers (2018); Freire (1996). Regarding the second theoretical axis, diversity, we mobilize the studies of authors such as Moreira and Candau (2008), Gomes (2007), Fleuri (2018), Arroyo (2021), Walsh (2007). This study has a qualitative nature, in the methodological field, it is guided by the approach of ethno research-training. The production of data was constituted by interviews and discussion group devices. To analyze and interpret the information produced, the interpretative methodology proposed by the Discursive Textual Analysis is used, as it allows the researcher the interpretations that print new understandings to the teaching narratives.The results can lead to understand that the dialogues established with and in a certain diversity disseminated in educative practice, are punctuals, being presented only in conflict situations, pointing to challenges on some themes approaches. The pedagogical treatment with the subjects of diversity, in a first time, was guided in a more respectful and accepting way, but it’s important to understand and debate the need for a work in the perspective of criticism. The variety of reading and writing practices that were accomplished to the collaborators’ educative process were potent didactic instruments that can reveal the students realities and singularities. They need to be more intentionally explored to guide the development of diversity and emancipatory pedagogy.